Theodor Lessing's philosophy of history in its time - Simissen, H. G. J. M. (Philosophy of history and culture ;, 2021)
"This study--the first full-length monograph in English on the subject--discusses the genesis of Theodor Lessing's philosophy of history as mainly expressed in his books "Geschichte als Sinngebung des Sinnlosen" (1919 and 1927), as well as its philosophical implications. Lessing on the one hand vehemently denies that historians can know the past as it actually happened. On the other hand, and rather surprisingly, he emphasizes the exceptional importance of history within a culture, because of what he calls its religious function. His penetrating analysis of history is remarkably relevant for ongoing debates on the very nature of history"--